Developmental Outcomes of Children Served in a Part C Early Intervention Program. Issue 1 (January 2022) - Elbaum, Batya; Celimli-Aksoy, Seniz
Abstract : In the United States, early intervention (EI) programs under Part C of the Individuals with Disabilities Education Act serve thousands of infants and toddlers with or at risk for developmental delays. Despite this, few studies have investigated the developmental progress and outcomes of children served, especially in relation to the heterogeneity of children's diagnoses and identified areas of delay. In this study, we classified children into 9 subgroups based on their medical diagnosis or, for children without a specific diagnosis, their identified areas of developmental delay. We then analyzed data from the developmental assessment administered to each child on program entry and exit. Multivariate analyses of children's pre- and postscores in 5 domains (cognitive, motor, adaptive, communication, and personal–social) confirmed the distinctiveness of each subgroup's developmental profile on entry into EI as well as significant differences across subgroups in children's pattern of developmental change while in services. Across subgroups, the percentage of children who were within age norms in all measured domains at the time they transitioned out of the program ranged from 10% to 49%. The results add to our understanding both of children's improvements while in EI and the variation in outcomes for meaningfully defined subgroups of children.